2021
DOI: 10.3390/jcm10102171
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Frailty in Geriatric Patients as a Prognostic Factor in Endovascular Treated Patients with Large Vessel Occlusion Strokes

Abstract: Frailty is associated with an increased risk of adverse health-care outcomes in elderly patients. The Hospital Frailty Risk Score (HFRS) has been developed and proven to be capable of identifying patients which are at high risk of adverse outcomes. We aimed to investigate whether frail patients also face adverse outcomes after experiencing an endovascular treated large vessel occlusion stroke (LVOS). In this retrospective observational cohort study, we analyzed patients ≥ 65 years that were admitted during 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 24 publications
0
17
0
1
Order By: Relevance
“…There was considerable heterogeneity across the included studies in the tool used to assess frailty and how this was defined and classified ( Table 3 ). Seven studies used an approach based on frailty index (varying number of items included, range: 4–33; [ 14–17 , 20 , 24 , 25 ]) four studies used the Hospital Frailty Risk Score [ 19 , 22 , 23 , 28 ], albeit with differing terminology for the included categories; two used the Fried phenotype approach [ 25 , 27 ], one used pre-stroke mRS [ 21 ] and one study used the Clinical Frailty Scale (CFS; [ 13 ]). One study compared two measures of frailty in the same cohort, a 33-item frailty index and the Fried frailty phenotype, although there was substantial missing phenotype data [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…There was considerable heterogeneity across the included studies in the tool used to assess frailty and how this was defined and classified ( Table 3 ). Seven studies used an approach based on frailty index (varying number of items included, range: 4–33; [ 14–17 , 20 , 24 , 25 ]) four studies used the Hospital Frailty Risk Score [ 19 , 22 , 23 , 28 ], albeit with differing terminology for the included categories; two used the Fried phenotype approach [ 25 , 27 ], one used pre-stroke mRS [ 21 ] and one study used the Clinical Frailty Scale (CFS; [ 13 ]). One study compared two measures of frailty in the same cohort, a 33-item frailty index and the Fried frailty phenotype, although there was substantial missing phenotype data [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mortality: seven studies examined the association between frailty status and mortality risk over a range of follow-up periods [ 13 , 15 , 16 , 20 , 21 , 23 , 28 ]. Two studies specifically considered in-hospital mortality and found no association with frailty, using a frailty index and the HFRS [ 20 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations